PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR MATEMATIKA SISWA GRUP VIII SMPN 43 PADANG - Frateissia, Feizzi (Jurnal Edukasi dan Penelitian Matematika, 2025)
Abstract — This study aim to determine the effect of the Think Pair Share (TPS) learning model on mathematical learning outcomes of VIII grade students of SMPN 43 Padang. This research is classified as experiment research with a randomized posttest control-group-only design. The population in this study amount to 88 people. Determination of the sample in this study use random sampling of 62 students, where experimental class consisted of 32 people and control class as many as 29 classes. Data analysis using ANOVA. In this research, the final test was given in the form of an essay, and after the t-test was obtained P-value = 0.016. Because P-value <0.05 consequently reject . The result show that there were differences in mathematics learning outcomes between student who used Think Pair Share (TPS) type learning model with student who used direct learning models in class VIII students of SMPN 43 Padang.Keywords —Think Pair Share, Understanding of Mathematical Concept, Direct Learning.